A Contribution to the Non-Static Theory of Choice - Tintner, Gerhard (Quarterly Journal of Economics, 1942)
The problem, 274. — Subjective risk, 275. — Subjective uncertainty, 280. — Graphical illustrations, 281. — Methodological considerations, 301. — Empirical verification, 302. — Relation to welfare economics and economic policy, 305.